T Cell‐Mediated Transport of Polymer Nanoparticles across the Blood–Brain Barrier - Ayer, Maxime; Schuster, Markus; Gruber, Isabelle; Blatti, Claudia; Kaba, Elisa; Enzmann, Gaby; Burri, Olivier; Guiet, Romain; Seitz, Arne; Engelhardt, Britta; Klok, Harm‐Anton (Advanced healthcare materials, 2021)
Delivery of therapeutics to the central nervous system (CNS) is challenging due to the presence of the blood–brain barrier (BBB). Amongst various approaches that have been explored to facilitate drug delivery to the CNS, the use of cells that have the intrinsic ability to cross the BBB is relatively unexplored, yet very attractive. This paper presents a first proof‐of‐concept that demonstrates the feasibility of activated effector/memory CD4+ helper T cells (CD4+ TEM cells) as carriers for the delivery of polymer nanoparticles across the BBB. This study shows that CD4+ TEM cells can be decorated with poly(ethylene glycol)‐modified polystyrene nanoparticles using thiol–maleimide coupling chemistry, resulting in the immobilization of ≈105 nanoparticles per cell as determined by confocal microscopy. The ability of these cells to serve as carriers to transport nanoparticles across the BBB is established in vitro and in vivo. Using in vitro BBB models, CD4+ TEM cells are found to be able to transport nanoparticles across the BBB both under static conditions as well as under physiological flow. Finally, upon systemic administration, nanoparticle‐modified T cells are shown to enter the brain parenchyma of mice, demonstrating the brain delivery potential of this T cell subset in allogeneic hosts. CD4+ helper T cells can be surface‐modified via thiol–maleimide chemistry with polymer nanoparticles. These modified cells can act as carriers that allow for the transport of the nanoparticle cargo across the blood–brain barrier both in vitro as well as in vivo.